Use of Chitosan to Control Vibrio harveyi Infection on White Shrimp Litopeneaus vannamei - . Sukenda; Y. Tri Anggoro; D. Wahjuningrum; . Rahman (Jurnal Akuakultur Indonesia)
Immunostimulation and antibacterial effect of chitosan against vibriosis were examined in white shrimp (Litopenaeus vannamei).  Control shrimps were injected with 0.05 μl of sterile sea water, while experimental shrimps were injected with 2, 4 and 6 μg per g shrimp of chitosan.  All shrimps were subsequently challenged by 106 CFU/ml of live Vibrio harveyi by injection method.  Survival rate of shrimps injected with chitosan were found to slightly increase in accordance with dose of chitosan, even not statistically significant.  Total haemocyte count and phagocytic index at experimental shrimps were over than control shrimps up to three days post injection.  Number of V. harveyi in the intestine of experimental shrimps were lower than control shrimps indicates an antibacterial activity of chitosan to combat infection.